Pertussis vaccination in mixed markets: Recommendations from the Global Pertussis Initiative - Chitkara, Amar J. (2020)
The Global Pertussis Initiative is an expert scientific forum that publishes consensus recommendations concerning pertussis for many regions of the world. Here, we give recommendations for the primary vaccination of infants in those countries where whole-cell pertussis (wP)- and acellular pertussis (aP)-containing combination vaccines are used in parallel. A selective literature review was performed concerning the influence on safety, immunogenicity, and effectiveness of mixing wP- and aP-containing vaccines for primary immunization of infants. In addition, local data were collected from various countries and the results discussed in a face-to-face meeting. Very few data addressing issues of mixing combination vaccines were identified, and no data were available concerning the effectiveness or duration of protection. It was also found that pharmacovigilance data are scarce or lacking in those countries where they would be needed the most. We then identified frequent problems occurring in low- and middle-income countries (LMICs) where both vaccine types are used. Relying on local knowledge, we give practical recommendations for a variety of situations in different settings. Specific needs for additional data addressing these issues were also identified. International bodies, such as the World Health Organization (WHO), as well as vaccine producers should try to find ways to highlight the problems of mixing wP- and aP-containing combination vaccines with robust data. Countries are urged to improve on their pharmacovigilance for vaccines. For practicing physicians, our recommendations offer guidance when wP- and aP-containing vaccines are used in parallel during primary immunization.